Dengue prevention: implications of the meshes used in household water reservoirs for Aedes aegypti control - Leandro Nunes Serpa, Lígia (2010)
The objective of this paper is to all attention to the strategy of covering water reservoirs for human consumption as a means to achieve Aedes aegypti control. During control activities carried out between 2004 and 2008, observation focused on methods of installation and maintenance of the meshes used in the covered of the reservoirs were observed, as well as the presence of Aedes aegypti larvae. The majority of the meshes on the water reservoirs were in direct contact with water, with brittle and dried appearance due to weathering. In both situations, the water reservoirs (77.5%) contained a high number of immature Aedes aegypti. The condition of breeding places in human habitations and the use of meshes require constant preventive practices from the population to reduce the contribution of breeding places to produce the vector Aedes aegypti. We highlight the need for greater attention to the way of placement, durability, type of fabric and the participation of the population.